Tingkat Stres Orang Tua dengan Kecemasan Sosial Pada Anak di Wilayah Kecamatan Sukun RT. 03 Kelurahan Tanjungrejo - Hastutiningtyas, Wahidyanti Rahayu; rosdiana, yanti (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Stress is the body's reaction to various demands of life and may become the triggering factor in the emergence of disorders or diseases. Parents who experience stressful conditions will affect social anxiety in children. Stress is hard to avoid in life. Social anxiety in children can occur due to the parent's experience of stress. The study aimed to determine the relationship between parents' stress and social anxiety levels among children in Sukun District, Malang City. The design of the research was analytic observation with cross-sectional. The instrument used was a stress and social anxiety level questionnaire. The sampling technique was simple random sampling. The population in this study was 40 parents who live in the Sukun District RT 03, and 32 respondents were included as study participants. The results of the Spearman-rank test showed a relationship between parents' stress and social anxiety levels among children in Sukun District with p = 0.000 (p 0.05). This study concludes that the respondents have high stress and mild social anxiety in children.